1960
DOI: 10.1002/macp.1960.020400110
|View full text |Cite
|
Sign up to set email alerts
|

Der abbau von polyoxymethylenen. Poloxymethylene. 14. Mitteilung

Abstract: ZUSAMMENFASSUNG:Quantitative Untersuchungen uber die Zersetzung von Polyoxymethylenen unter verschiedenen Bedingungen eeigen, daB im wesentlichen 5 Abbaureaktionen unterschieden werden konnen 1. Depolymerisation vom Kettenende her, 2. .4utoxydative Spaltung, 3. Abbau durch Sekundarprodukte der Autoxydation, 4. Thermische Degradation, 5 . Hydrolyse und Acidolyse. Die einzelnen Reaktionen lassen sich experimentell getrennt untersuchen. Es werden Moglichkeiten angegeben, den Abbau zu unterdriicken. Eine Methode z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1967
1967
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…In accordance with the mechanism adopted here the chain ends are not involved in the degradation process. This suggestion was supported by the observation [1,16] that no change should occur in the intensity of the carbonyl bands at 1750 cm -1 due to ester end groups. The authors of [1] and [16] observed an increase in C = O/~/~/absorption which constitutes additional ) H evidence of the formation of fairly long, relatively stable chains.…”
Section: Ir Studies Of Polyoxymethylene Therrnooxidationmentioning
confidence: 51%
See 1 more Smart Citation
“…In accordance with the mechanism adopted here the chain ends are not involved in the degradation process. This suggestion was supported by the observation [1,16] that no change should occur in the intensity of the carbonyl bands at 1750 cm -1 due to ester end groups. The authors of [1] and [16] observed an increase in C = O/~/~/absorption which constitutes additional ) H evidence of the formation of fairly long, relatively stable chains.…”
Section: Ir Studies Of Polyoxymethylene Therrnooxidationmentioning
confidence: 51%
“…This suggestion was supported by the observation [1,16] that no change should occur in the intensity of the carbonyl bands at 1750 cm -1 due to ester end groups. The authors of [1] and [16] observed an increase in C = O/~/~/absorption which constitutes additional ) H evidence of the formation of fairly long, relatively stable chains. They also observed additional changes in the 1275-1300 cm -1 region, which can be connected with the chain scission.…”
Section: Ir Studies Of Polyoxymethylene Therrnooxidationmentioning
confidence: 51%
“…The long term heat degradation of polyacetals is a combined process of oxidation and acidolysis [144][145][146][147]. In first instance polyacetals oxidizes according to the mechanism shown in Scheme 1, with the oxidation taking place at the methylene groups.…”
Section: -In Service Life Degradationmentioning
confidence: 99%
“…Formic acid, which can initiate an acidolytic chain scission, is formed as byproduct of the decomposition by oxidation of formaldehyde or by disproportionation. Acidic catalyst residues can also produce chain scission [98,99]; for further details, see [100].…”
Section: Additives 341 Stabilizersmentioning
confidence: 99%